Jurnal Penyuluhan: Analisis Kebutuhan Pelatihan Guru IPA Berbasis Kompetensi Kepribadian - Irma Febrianis, Pudji Muljono, Djoko Susanto (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Deviant behavior and ethic, norm, and moral violations done by the teachers become indicators on how poor is the personalcompetence of the teachers in Indonesia. Training to improve the personal competence of the teachers has got less concern fromthe government. This study offers an alternative in determining the training needs using the Training Needs Assessment (TNA)